A place-based assessment of biodiversity intactness in sub-Saharan Africa - Hayley S. Clements; Reinette Biggs; Alta De Vos; Emmanuel Do Linh San; Gareth P. Hempson; Birthe Linden; Bryan Maritz; Ara Monadjem; Chevonne Reynolds; Frances Siebert; Nicola Stevens; Matthew Child; et al. (Nature, 2026)
Abstract Maintaining biodiversity is central to the sustainable development agenda 1 . However, a lack of context-specific biodiversity information at policy-relevant scales has posed major limitations to decision-makers 2,3 . To address this challenge, we undertook a comprehensive assessment of the biodiversity intactness of sub-Saharan Africa 4 using place-based knowledge of 200 African biodiversity experts 5 . We estimate that the region has on average lost 24% of its pre-colonial and pre-industrial faunal and floral population abundances, ranging from losses of <20% for disturbance-adapted herbaceous plants to 80% for some large mammals. Rwanda and Nigeria are the least intact (<55%), whereas Namibia and Botswana are the most intact (>85%). Notably, most remaining organisms occur in unprotected, relatively untransformed rangelands and natural forests. Losses in biodiversity intactness in the worst-affected biomes are driven by land transformation into cropland in grasslands and fynbos (Mediterranean-type ecosystems), by non-agricultural degradation in forests and by a combination of the two drivers in savannas. This assessment provides decision-makers with multifaceted, contextually appropriate and policy-relevant information on the state of biodiversity in an understudied region of the world. Our approach could be used in other regions, including better-studied localities, to integrate contextual, place-based knowledge into multiscale assessments of biodiversity status and impacts.